Accounting for Cross-Country Income Differences : Ten Years Later - Caselli, Francesco (World Bank, Washington, DC, 2017)
The study focused on a cross-section of countries observed in the mid-1990s, so the conclusions from that e¤ort are beginning to be a bit dated. In addition, signi cant revisions of the data underlying the 2005 paper have been published. Last but not least, in the intervening years become aware of ways in which the original methodology can be usefully improved and extended. Hence the present update and upgrade of the original paper. This paper focuses on data (mostly) from 2005 and improves on the original methodology in several dimensions. Development accounting compares di¤erences in income per worker between developing and developed countries to counter-factual di¤erences attributable to observable components of physical and human capital. Such calculations can serve a useful preliminary diagnostic role before engaging in deeper and more detailed explorations of the fundamental determinants of di¤erences in income per worker. The research and policy agenda would then have to focus on technology, allocative e¢ ciency, competition, and other determinants of the efficient use of capital. However because of limitations in thecoverage of the test results, author also present results where human capital is only measured from years of schooling and health. It turns out that, at least in my preferred calibration, the addition or omission of cognitive skills (as measured by test scores) does not greatly affect the quantitative results.